2012
DOI: 10.1186/1471-2164-13-316
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of genic-SSR markers in sesame by RNA-seq

Abstract: BackgroundSesame (Sesamum indicum L.) is one of the most important oil crops; however, a lack of useful molecular markers hinders current genetic research. We performed transcriptome sequencing of samples from different sesame growth and developmental stages, and mining of genic-SSR markers to identify valuable markers for sesame molecular genetics research.ResultsIn this study, 75 bp and 100 bp paired-end RNA-seq was used to sequence 24 cDNA libraries, and 42,566 uni-transcripts were assembled from more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
96
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(124 citation statements)
references
References 45 publications
22
96
6
Order By: Relevance
“…In this study, dinucleotide SSRs were the most abundant (36 %), which is in accordance with results reported for sesame (Zhang et al, 2012) and some Rosaceae species (Jung et al, 2005). However, in most other fruit species and crop plants, trinucleotide repeats have been observed at the highest frequency (Jian et al, 2012;Liu et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, dinucleotide SSRs were the most abundant (36 %), which is in accordance with results reported for sesame (Zhang et al, 2012) and some Rosaceae species (Jung et al, 2005). However, in most other fruit species and crop plants, trinucleotide repeats have been observed at the highest frequency (Jian et al, 2012;Liu et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…The weak correlation coefficient for the two clustering matrices by a Mantel test showed an insignificant correlation between phenotypic and molecular marker information. Zhang et al (2012) concluded that molecular measures of genetic diversity may not fully explain quantitative genetic variability. Therefore, the combination of phenotypic and molecular based analysis in genetic diversity assessment of the sesame appears to be momentous in developing any breeding program.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, there is often discrepancy among SSR density estimates reported for the same species by different authors. For example, while analyzing the same sequence data, the density of SSRs identified in sesame genic sequences decreased from one SSR per 6.6 to 10.8 kb, when the minimum SSR length was increased from 15 to 18 bases (Zhang et al, 2012). The average SSR density of the Arabidopsis thaliana (L.) Heynh.…”
Section: Simple Sequence Repeat Development and Validationmentioning
confidence: 99%
“…The trend also applied for trinucleotide SSRs with a predominance of AT-rich repeats, similar to our findings. Whether or not mononucleotide repeats are included in SSR surveys, all reports on genic SSR development in sesame indicate dinucleotide repeats as the predominant SSR type in coding sequences (Wei et al, 2008;Wei et al, 2011;Zhang et al, 2012;Yepuri et al, 2013;Wu et al, 2014). In addition, AG/CT was consistently found as the predominant motif in sesame genic SSRs.…”
Section: Simple Sequence Repeat Development and Validationmentioning
confidence: 99%
See 1 more Smart Citation